2018
DOI: 10.11648/j.ajae.20180501.13
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Vortex Shedding Behind an Airfoil-Spoiler Configuration

Abstract: Spoilers are widely used on aircrafts as lateral control devices. Despite their wide usage, very little numerical and theoretical information exist. Numerical simulation of the full unsteady, compressible Euler's equations over the NACA 23012 airfoil with spoiler is performed using a hybrid Least-Squares finite element/finite difference method coupled to the Newton-Raphson's linearization technique. The flow patterns behind the spoiler are presented. The pressure coefficient over the upper and lower surfaces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…From this study, it was found that as the spoiler is deflected, the change in lift between the airfoil with the spoiler compared to that without a spoiler increases, highlighting the spoiler's effectiveness. There have also been numerous computational and experimental studies [9][10][11][12][13][14][15][16][17][18][19] investigating the effect of spoiler position, spoiler deflection angle, and spoiler chord on the aerodynamic characteristics of different airfoil geometries. Mashud et al [9] investigated a NACA2415 airfoil equipped with spoilers located at 0.5C, 0.6C, 0.7C, 0.8C, and 0.9C to determine the spoiler's effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this study, it was found that as the spoiler is deflected, the change in lift between the airfoil with the spoiler compared to that without a spoiler increases, highlighting the spoiler's effectiveness. There have also been numerous computational and experimental studies [9][10][11][12][13][14][15][16][17][18][19] investigating the effect of spoiler position, spoiler deflection angle, and spoiler chord on the aerodynamic characteristics of different airfoil geometries. Mashud et al [9] investigated a NACA2415 airfoil equipped with spoilers located at 0.5C, 0.6C, 0.7C, 0.8C, and 0.9C to determine the spoiler's effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the typical vortex shedding behavior of a spoiler was similar to that of bluff body shedding. The flow field was characterized by a highly turbulent fluctuating wake, and the strength of the wake increased with a spoiler deflection angle [13,14]. Askar et al [15] investigated numerically, using Ansys14 software, the effect of the spoiler position, and the gap between the spoiler and wing.…”
Section: Introductionmentioning
confidence: 99%